Geophysical Analysis Using Proton Precession Magnetometer GSM-19T as Information on Fault Presence in Medana, North Lombok, Indonesia - Haerul Anwar; Vico Luthfi Ipmawan; Thanaporn Sriyakul (CV FOUNDAE, 2022)
Lombok island is included in one of the areas prone to earthquakes due to the existence of a subduction zone resulting from the meeting of the Indian-Australian Plate. In this study, the magnetic method was used to determine the subsurface structure of the fault as a research objective. The instrument used in this study consisted of a Proton Precession Magnetometer GSM-19T v7.0 Geomagnet measuring instrument with an accuracy of 0.1 nT to measure the total magnetic field strength. Garmin 60CSx GPS to determine position (latitude and longitude), elevation, time and point of measurement location. The geological compass determines the position and direction of the north-south fault which includes the dip/strike. Some software is also used in processing this geomagnetic data, namely Software (Numeri, Mag2DC, Surfer 9.0) and MS Excel 2013. Based on the results of data processing with 2D and Mag2DC forward modeling, the subsurface structure is obtained in the form of a normal fault, with the average susceptibility value is 0.00605 in Susceptibility (SI) which is a type of limestone. The depth of this normal fault is estimated to be at a depth of 31.5 meters to 74.0 meters.